Minimising risks for South Australia's legal interns. (June 2023) - Hewitt, Anne; Henderson, Stacey; Covark, Kylie
Australia's legal profession is currently undergoing a long-awaited reckoning as professional representative bodies, law firms and courts craft solutions to the embedded culture of sexual harassment. But what of the other exclusionary and inequitable practices in legal workplaces? This article considers a project to minimise the myriad risks for legal interns in South Australia. By educating both law students and placement hosts about interns' rights, and how lawyers from a range of backgrounds can be supported to succeed, we hope to facilitate equitable and successful participation in legal work experience for a new generation of diverse and inclusive practitioners.